(untitled) (Contemporary Journal of Social Science Review, 2025)
The rapid expansion of Artificial Intelligence (AI) has transformed the production, organization, and dissemination of knowledge across academic disciplines. In the field of Islamic studies, digital platforms and encyclopaedic resources now play a central role in shaping contemporary scholarly authority and public understanding. This study critically examines the impact of AI on Islamic encyclopaedic scholarship, with a particular focus on Brill’s Encyclopaedia of Islam as a foundational reference work in modern Islamic studies. The research explores how AI-driven technologies influence the preservation of authenticity, the construction of scholarly authority, and the reinterpretation of classical Islamic knowledge in the digital age. By integrating perspectives from Islamic epistemology, digital humanities, and knowledge ethics, this study analyzes both the opportunities and challenges presented by AI in the context of encyclopaedic knowledge production. The article argues that while AI offers unprecedented possibilities for accessibility, organization, and interdisciplinary research, it also raises critical concerns regarding textual integrity, interpretive bias, and the future role of human scholarship. Through qualitative textual analysis and comparative evaluation, this research contributes to an emerging academic discourse on the intersection of technology and Islamic intellectual traditions. It proposes a balanced framework for integrating AI into Islamic encyclopaedic scholarship while safeguarding the principles of authenticity, scholarly rigor, and ethical responsibility.